Continent anal urinary diversion in classic bladder exstrophy: 45-year experience - Rubenwolf, Peter; Stein, Raimund (Urology, 2017)
Objective: To evaluate the long-term outcomes in patients with classic bladder exstrophy and continent anal urinary diversion (CAD) for continence, upper urinary tract status, secondary malignancies, and sexual function. Patients and Methods: The medical records of 82 exstrophy patients having undergone CAD in our department between 1970 and 2015 were reviewed. Patients were invited for follow-up examinations and asked to complete validated questionnaires relating to sexual function. Results: Thirty-two of 57 eligible patients with a median follow-up of 23.9 years were included in the study. Ninety-seven percent of patients were fully continent during daytime. Upper urinary tract and renal function remained stable in 75% and 87%, respectively. Five patients developed secondary malignancies originating from the rectal reservoir. Forty-one percent received prophylactic alkaline substitution. Sexual function as measured by the Female Sexual Function Index and the International Index on Erectile Function was negatively affected in all domains in both genders. Eighty-six percent of patients had a stable relationship and 35% were married. Five women conceived a total of 6 healthy children. Paternity rate was 40%. Conclusion: CAD constitutes an effective treatment option with acceptable long-term outcomes in exstrophy patients in whom all attempts at restoring the lower urinary tract have failed. Long-term follow-up of the upper urinary tract, assessment of acid-base balance, and endoscopy of the rectosigmoid reservoir are paramount for the safety of this type of management. Evaluation of sexual dysfunction should be an active part of follow-up.